KAJIAN TENTANG PERILAKU PENGGUNA E-FAKTUR WEB-BASED MELALUI PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Adhitya Putri Pratiwi; Aris Sanulika (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
This study aims to measure the extent to which taxpayers feel helped by the presence of e-faktur web-based, where to measure this the researcher uses perceived usefulness and perceived ease of use as indicators, and this research is expected to provide input for policymakers, in this case the Directorate General of Taxes regarding deficiencies or difficulties faced by taxpayers in using e-faktur web-based. The population used in this study is web-based e-invoice users and the sampling technique used is snowball sampling where the researcher chooses several research colleagues to be able to help distribute questionnaires to other respondents with the criteria determined by the researcher, namely the respondent is a taxpayer who has reported the Periodic Value Added Tax (VAT) SPT using a web-based e-invoice. This study uses a quantitative approach with primary data. The data collected was then processed using SPSS Version 25 with the Multiple Linear Regression method. This study shows the results that perceived usefulness influences on the attitude of taxpayers towards the use of e-faktur web-based, while the perception of convenience does not influence on the attitude of taxpayers towards the use of e-faktur web-based. This research is expected to be an input for policymakers, especially the Directorate General of Taxes, which is currently very aggressively reforming tax administration to provide convenience for taxpayers in fulfilling their tax compliances.